Role of Exogenous Carbohydrate and Amino Acid Sources on Biomass and Colchicine Production in Nontransformed Root Cultures of Gloriosa superba - Ghosh, Seemanti; Ghosh, Biswajit; Jha, Sumita (Plant Tissue Culture and Biotechnology, 2016)
Elicitation strategies were studied for yield enhancement of colchicine, produced by root cultures of Gloriosa superba. Adventitious root cultures were established and grown in media containing 3 mg/l NAA and 1 mg/l BA. Root cultures showed variations in biomass as well as colchicine production in the presence of different exogenous carbohydrates and amino acid. Among the different sources of carbohydrates used - fructose, sucrose and dextrose gave a substantially higher biomass yield than the control. Maximum biomass was obtained in the presence of fructose. Root cultures growing in mannitol supplemented medium resulted in maximum accumulation of colchicine (0.32%). Among the amino acids, serine and phenylalanine significantly enhanced colchicine accumulation in root cultures. 0.02 mM glutamine supplemented media showed maximum (ten-fold) increase of root biomass. Plant Tissue Cult. & Biotech. 25(2): 247-256, 2015 (December)